1989
DOI: 10.1254/jjp.50.167
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of the neurotropic mycotoxin fumitremorgin A in the rabbit. () Effects on the spinal cord.

Abstract: Abstract-Effects of a potent neurotropic mycotoxin, fumitremorgin A (FTA), on the spinal cord were studied, using rabbits lightly anesthetized with urethane and chloralose.Spontaneous discharges of L7 spinal ventral roots and common peroneal nerves were increased after intravenous injection of 100-200 ug/kg of FTA. Their abnormal discharge pattern represented the convulsive effect of FTA. Spinal monosynaptic reflexes became irregular in amplitude, with a slight predominance of smaller reflexes.Polysynaptic ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…Since this area of the reticular formation is considered to be a part of the brain stem facilitatory areas proposed by Lindsley et al (7), it is likely that the FTA-induced genera lized tonic-clonic convulsion is a con sequence of excessively increased activity of the reticulospinal facilitatory pathways. This assumption is also supported by the previous observation that FTA failed to cause con vulsion after spinalization (4).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Since this area of the reticular formation is considered to be a part of the brain stem facilitatory areas proposed by Lindsley et al (7), it is likely that the FTA-induced genera lized tonic-clonic convulsion is a con sequence of excessively increased activity of the reticulospinal facilitatory pathways. This assumption is also supported by the previous observation that FTA failed to cause con vulsion after spinalization (4).…”
Section: Discussionsupporting
confidence: 80%
“…In previous studies, the main site of con vulsant action of FTA has been suggested to be in some restricted areas in the brain stem, from the mesencephalon to the medulla oblongata (3,4). In the present study, the role of the brain stem in the convulsant effect of FTA was investigated in anesthetized rabbits.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Fumitremorgin C (FTC) was the first identified selective inhibitor of ABCG2, completely reversing mitoxantrone resistance in ABCG2 cells. This natural product was isolated from Aspergillus fumigatus , but turned out to be clinically useless owing to its neurotoxicity . Based on the indolyl diketopiperazine moiety, several structurally related analogues were developed, especially the less toxic and more potent inhibitor Ko143, the clinical use of which is limited by metabolic instability due to its Boc‐ester group .…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal activation of these cells by the mycotoxin could in turn lead to convulsive burst discharges in peripheral motor nerves. This may account for the typical epileptogenic effect of fumitremorgin A (Nishiyama and Kuga, 1989;Nishiyama and Kuga, 1990). A similar effect was exerted also by verruculogen (Bikson et al, 2002).…”
Section: Indole Alkaloidsmentioning
confidence: 77%